The Belgian Iron and Steel Industry in the International Context - Frédéric Lagneaux; David Vivet (National Bank of Belgium, 2009)
This paper provides a survey of the main developments in the iron and steel industry over the last few decades. The first chapter covers the changing conditions on international markets and identifies the main challenges facing the companies in this sector. These include the boom in China, the increasing prices of steel and raw materials, the wave of mergers and acquisitions as well as the implementation of environmental regulations, in particular the Kyoto Protocol. Against the backdrop of the worsening global economic crisis, market conditions for steel are also set to change markedly, at least in the medium term. The second chapter provides an assessment of the Belgian iron and steel sector's economic impact, in terms of direct value added, employment and investment. The chapter also includes an evaluation of the indirect effects of the sector, both upstream and downstream
Keywords: L61; L22; Q5; C67; J21; 330; branch survey; iron and steel industry; market structure; indirect effects; Stahlindustrie; Marktstruktur; Branchenentwicklung; Internationaler Wettbewerb; Belgien